2003
DOI: 10.1034/j.1600-0897.2003.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CD4‐independent HIV Receptors on Spermatozoa

Abstract: A 160 kDa sperm protein could be the CD4-independent HIV receptor for HIV to bind and enter into the spermatozoa. Further characterization of this 160 kDa HIV receptor on sperm will provide an insight in understanding the mechanism and probable mode of intervention or prevention of HIV transmission at the initial stage of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
2
17
0
1
Order By: Relevance
“…50–52 Others have shown that the HIV-1 envelope glycoprotein gp120 binds to spermatozoa, indicating that sperm may be a vehicle for viral dissemination to the upper FRT. 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…50–52 Others have shown that the HIV-1 envelope glycoprotein gp120 binds to spermatozoa, indicating that sperm may be a vehicle for viral dissemination to the upper FRT. 53,54 …”
Section: Discussionmentioning
confidence: 99%
“…CCR4 and CCR1 encoding mRNAs have also been reported [53] and another chemokine receptor, CX3CR1, is thought to be expressed in the tail of spermatozoa [141]. In addition, an unknown protein of 160kDa that binds to HIV gp120 in Western-blot experiments has been specifically identified in spermatozoa [9].…”
Section: • • • • Hiv-1 In the Semenmentioning
confidence: 93%
“…L'expression de CCR5 a récemment été observée à la surface d'une sous-population de spermatozoïdes [53] et d'autres récepteurs des chimiokines ont également été mis en évidence au niveau de ces cellules [54][55][56]. Une étude a montré en Western-blot la présence dans les spermatozoïdes d'une protéine capable de fixer la protéine d'enveloppe du VIH [57]. Il reste à déterminer si ce récepteur potentiel est exprimé à la surface des cellules.…”
Section: Spermatozoïdes Et Vihunclassified